2014
DOI: 10.1523/jneurosci.3541-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquilin-1 Protects Cells from Oxidative Stress and Ischemic Stroke Caused Tissue Injury in Mice

Abstract: Ubiquilin-1 (Ubqln1 or Ubqln), a ubiquitin-like protein, mediates degradation of misfolded proteins and has been implicated in a number of pathological and physiological conditions. To better understand its function in vivo, we recently generated transgenic (Tg) mice that globally overexpress mouse Ubqln in a variety of tissues and ubqln conditional knock-out mice. The Tg mice were viable and did not show any developmental or behavioral abnormalities compared with their wild-type (WT) littermates. When subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
77
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(85 citation statements)
references
References 39 publications
7
77
0
Order By: Relevance
“…Ubiquilin-1 is a ubiquitin-like protein also known as UBQLN1. It mediates degradation of misfolded proteins and contributes to brain protection from oxidative stress and ischemic stroke [26]. Surprisingly, ubiquitin C-terminal hydrolase L1, which removes ubiquitin and prevents protein degradation, was also overexpressed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ubiquilin-1 is a ubiquitin-like protein also known as UBQLN1. It mediates degradation of misfolded proteins and contributes to brain protection from oxidative stress and ischemic stroke [26]. Surprisingly, ubiquitin C-terminal hydrolase L1, which removes ubiquitin and prevents protein degradation, was also overexpressed.…”
Section: Discussionmentioning
confidence: 99%
“…β-Amyloid is produced from amyloid precursor protein (APP) by TMP21, a member of the presenilin complex [42]. The observed accumulation of β-amyloid peptide (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) in penumbra could be also neurotoxic.…”
Section: Discussionmentioning
confidence: 99%
“…To generate the LV-Ublqn, we replaced the cDNA encoding GFP in the pLenti-CMV-GFP plasmid (Campeau et al 2009) with a full length mouse Ubqln cDNA sequence (Liu et al 2014b). The four different mouse LV-Ubqln-shRNAs and the scramble control were purchased from OriGene (Rockville, MD, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Our previous studies have revealed that ubiquilin1 (Ubqln) interacts with misfolded proteins and selectively enhances their degradation (Wang and Monteiro 2007). Our recent results suggest that Ubqln is a potential therapeutic target for ischemic stroke, as overexpression (OE) of Ubqln protects cells against oxidative stress and ischemia/reperfusion (I/R)-caused brain injury but knockout (KO) of the gene shows the opposite results (Liu et al 2014b). In these studies, however, alteration of Ubqln expression occurs prior to ischemic insults.…”
Section: Introductionmentioning
confidence: 99%
“…Transgenic mice globally over-expressing ubiquilin-1 exhibit resistance to oxidative stress and ischemia/reperfusion injuries in the CNS (Liu et al, 2014), which parallels the resistance of cd47 null mice to cerebral ischemia (Jin et al, 2009). CD47 and ubiquilin-1 also share roles in regulation of cytoplasmic calcium levels.…”
Section: Proximal Signalingmentioning
confidence: 99%